Modifying The KL Barombong: Influence of Length Extension on Speed, Resistance, and Fuel Consumption - Adnan, Adnan; Sunusi, Sahabuddin; Bakar, Abu; Saleh, Muhammad; Sutanto, Heri (Institut Teknologi Sepuluh Nopember, 2024)
This study investigates the effects of extending the hull length of the KL Barombong training vessel, specifically on speed resistance, engine power requirements, propeller efficiency, and fuel consumption. The objective is to assess how these modifications impact overall vessel performance, particularly fuel efficiency and operational costs. Using Maxsurf simulation software, we analyzed the vessel's performance before and after the modification. Results show that extending the hull increased hydrodynamic resistance, requiring more engine power and raising fuel consumption by 12-15%. Additionally, the propeller efficiency declined due to the higher load. These findings emphasize the need for engine-propeller optimization during vessel modifications to ensure operational efficiency and sustainability. Recommendations for future modifications and system upgrades are also provided.